A critical review of the common ownership literature - Kristopher Gerardi; Michelle Lowry; Carola Schenone (Federal Reserve Bank of Atlanta, 2023)
The rapid growth in index funds and significant consolidation in the asset-management industry over the past few decades has led to higher levels of common ownership and increased attention on the topic by academic researchers. A consensus has yet to emerge from the literature regarding the consequences of increased common ownership on firm behavior and market outcomes. Given the potential implications for firms and investors alike, it is perhaps not surprising that policymakers, legal scholars, finance and accounting academics, and practitioners have all taken a keen interest in the subject. This paper provides an overview of the theoretical underpinnings of common ownership and critically reviews the empirical literature. Measurement issues and identification challenges are detailed, and a discussion of plausible causal mechanisms is provided. Across the newest papers employing the most credible identification techniques, there is relatively little evidence that common ownership causes lower competition. However, further research is necessary before broad conclusions can be reached.
Keywords: G23; G32; G34; L22; 330; common ownership; institutional investors; corporate governance